An ecosystem approach to circular economy implementation and efficiency: A global comparative analysis - Suryo, Kevin Ibrahim (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: This study examines Indonesia’s adoption of circular-economy (CE) principles through an ecosystem lens and benchmarks national progress against leading global models. Method: Drawing on a review of academic articles, policy reports, and case studies, nine Indonesian initiatives are cataloged, ranging from Mycotech Lab’s biowaste valorization to PT Pertamina’s circular-carbon programs and community-driven collaborations like LTKL. Findings: These examples demonstrate localized successes in waste reduction, resource recirculation, and stakeholder engagement, yet they remain largely sector-specific and pilot-scale. In contrast, regions such as the European Union, China, and Finland operate under comprehensive, economy-wide frameworks with binding targets, dedicated financing mechanisms, and mandatory extended-producer-responsibility schemes. Quantitative metrics from Indonesian projects show material savings (e.g., 2,200 tons of plastic avoided by BulkSource) and emission reductions (e.g., 352,000 ton CO₂eq cut by Pertamina). Meanwhile, qualitative analysis highlights enabling factors, including multi-stakeholder collaboration and eco-innovation; as well as persistent barriers such as policy fragmentation, limited funding, and uneven data availability. A cross-case synthesis shows the absence of harmonized indicators and national coordination, which hinders scaling and aggregation of sectoral gains into systemic impact. Conclusion: It is concluded that Indonesia’s transition to a mature CE requires the establishment of a coherent national roadmap with clear targets, robust monitoring, and inclusive governance structures that integrate informal and rural actors. Strengthening financial instruments, such as green bonds and blended-finance vehicles, and embedding circular criteria in public procurement will be critical to mobilizing investment and promoting widespread adoption. By aligning policy, finance, and community engagement, progress toward systemic circularity can be accelerated. Novelty/Originality of this Article: This study uniquely integrates ecosystem-based evaluation with quantitative and policy-level benchmarking to propose a strategic roadmap for Indonesia’s systemic CE transition.